Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1159/000321222
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Secondhand Tobacco Smoke Enhances Respiratory Symptoms and Responses to Animals in 8,819 Children in Kindergarten: Results from 25 Districts in Northeast China

Abstract: Background: Experimental data suggest that asthma exacerbation by allergens is enhanced by exposure to environmental tobacco smoke (ETS); however, there is little supporting epidemiologic evidence. To our knowledge, few studies have assessed respiratory symptoms and allergies in this context. Objectives: To evaluate whether the association of exposure to animals (indicators of allergen and endotoxin exposure) with asthma-related symptoms is modified by ETS exposure in Chinese children. Methods: A cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 58 publications
1
16
0
2
Order By: Relevance
“…Active and passive smoking are known to be risk factors for asthma [24]. An important positive environmental change experienced in Israel has been a decrease in the prevalence of cigarette smokers [25].…”
Section: Discussionmentioning
confidence: 99%
“…Active and passive smoking are known to be risk factors for asthma [24]. An important positive environmental change experienced in Israel has been a decrease in the prevalence of cigarette smokers [25].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to adults, children are more vulnerable to SHS exposure because their respiratory and immune systems are not fully developed. An extensive body of evidence has shown that SHS exposure is associated with respiratory symptoms [2][3][4][5][6] and lung function [7][8][9][10] …”
Section: Introductionmentioning
confidence: 99%
“…Pregnant mothers need special attention as regards tobacco control strategies. Nevertheless, the underlying message of this study [4] is loud and clear -SHS exposure harms children, the most vulnerable, and they should have the right to be protected from it.…”
mentioning
confidence: 94%
“…In this issue of Respiration, Dong et al [4] report findings from a large cohort of 8,819 children (mean age = 4.7 years) sampled randomly from households based in 25 districts of Northeast China. They looked at different forms of respiratory symptoms: from persistent phlegm to current asthma, and from wheeze to doctor-diagnosed asthma both independently and then combined in the presence of childhood allergen and SHS exposure.…”
mentioning
confidence: 99%
See 1 more Smart Citation